From the Incretin Concept and the Discovery of GLP-1 to Today's Diabetes Therapy - Holst, Jens Juul (Frontiers in Endocrinology, 2019)
Researchers have been looking for insulin-stimulating factors for more than 100 years, and in the 1960ties it was definitively proven that the gastrointestinal tract releases important insulinotropic factors upon oral glucose intake, so-called incretin hormones. The first significant factor identified was the duodenal glucose-dependent insulinotropic polypeptide, GIP, which however, turned out not to stimulate insulin secretion in patients with type 2 diabetes. But resection experiments clearly indicated the presence of an additional incretin, and in 1986, an unexpected processing fragment of the recently identified glucagon precursor, proglucagon, namely truncated glucagon-like peptide 1 (GLP-1 7-36amide), was isolated from the gut and found to both stimulate insulin secretion and inhibit glucagon secretion. The peptide also inhibited appetite and food intake. Unlike GIP, this peptide had preserved effects in patients with type 2 diabetes and it was soon documented to have powerful antidiabetic effects in clinical studies. Its utility was limited, however, because of an extremely short half-life in humans, but this problem had two solutions, both of which gave rise to important antidiabetic drugs: 1) orally active inhibitors of the enzyme dipeptidylpeptidase 4 (DPP-4 inhibitors ), which was responsible for the rapid degradation; the inhibitors protect endogenous GLP-1 from degradation and thereby unfold its antidiabetic activity, and 2) long-acting injectable analogs of GLP-1 protected against DPP-4 degradation. Particularly, the latter, the GLP-1 receptor agonists, either alone or in various combinations, are so powerful that treatment allows more than 2/3 of type 2 diabetes patients to reach glycemic targets. In addition, these agents cause a weight loss which, with the most successful compounds, may exceed 10 % of body weight. Most recently they have also been shown to be renoprotective and reduce cardiovascular risk and mortality.